Small-Bowel Myeloid Sarcoma Presenting as A Relapse Case of Acute Myeloid Leukemia - Shirazi, Nadia; Saxena, Akriti; Das, Kunal; Shrivastava, Vikas (Annals of Pathology and Laboratory Medicine, 2018)
Granulocytic sarcoma is an extramedullary tumor of primitive granulocytic cells. It can develop at any anatomic site and is often a prelude to the development of Acute Myelogenous Leukaemia. Granulocytic sarcoma of the small intestine presents with abdominal pain and obstruction. We report a case of a 17 year old boy who presented with epigastric pain. His endoscopy revealed nodular duodenal mucosa and an area of ulcerated exophytic growth in the small bowel. Histopathology and flow cytometery confirmed the diagnosis of granulocytic sarcoma associated with acute myelogenous leukaemia. This case merits interest because of rarity of presentation and thorough clinical and laboratory work up.